Pengaruh Kompensasi dan Work-Life Balance Terhadap Kinerja Karyawan Generasi Z Dimediasi Kepuasan Kerja - Wijaya, Piter Tanto; Purmono, Bintoro Bagus; Jaya, Arman; Yakin, Ikram (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study investigates the influence of compensation and work-life balance on the employee performance of Generation Z in coffee shops across Pontianak, with job satisfaction acting as a mediating variable. A quantitative descriptive approach was applied, using an explanatory causal research design. Data were gathered through an online questionnaire measured on a five-point Likert scale. The questionnaire was distributed to 170 coffee shop employees in Pontianak, aged between 18 and 27 years, selected through purposive sampling. The analysis was conducted using SEM-PLS with SmartPLS 4. The findings indicate that compensation and work-life balance both have a significant positive effect on employee performance, and that job satisfaction mediates the relationship between these variables and performance.